Microstylis muscifera (Jeevak): Highly Therapeutic and Endangered Orchid - RG Singhal3, Parveen Bansal1*Richa Raturi1, Gunpreet Kaur1 Vikas Gupta1, Mukesh Maithani2 (Journal of Biomedical and Pharmaceutical Research, 2017)
In ancient times, Ashwani Kumars (Ayurvedic wonder healers) have been said to see the old, frail and emaciated body of Rishi Chyawan and decided to rejuvenate his body through medication by incorporating Ashtawarga, a group of eight medicinal plants in a “Leham” (a semi solid formulation) and did the miracle of rejuvenating the body of Rishi Chyawan as youthful. Since then after the name of Rishi Chyawan, the preparation was called as Chyawanprash and has been a favorite and most demanded medicine for Kings and rich people. Microstylis muscifera is one of the important plants of Ashtawarga group. Department of AYUSH has suggested use of substitutes in formulations in absence of original plants however this option is being exploited by manufacturers rendering this precious plant in ignored condition. Hence it becomes important to highlight the therapeutic potentials of this plant in front of scientists so that a justified research is carried out on an important but ignored plant. A limited data with scientific evidences are available in modern literature/internet sources; whereas old texts show valuable evidences in regional languages or in Sanskrit. Hence real uses of the plant are not well understood by scientific fraternity. Purpose of this compilation is to bring all the therapeutic potentials at a single platform so as to enable scientists working on these plants to know the scientific clues available in ancient literature. The compilation reflects multiple uses of plant active components in a number of Ayurvedic formulations useful in plethora of disorders. Keywords: Jeevaka, Ashtawarga, Anti-aging, Rejuvenative